Unveiling Ecological Vulnerability: multimodal construction of cascade effect strategy in Greenpeace’s video narratives - Krysanova, Tetiana (University of Latvia, 2024)
In the contemporary environmental discourse, the effective communication of ecological vulnerability plays a pivotal role in shaping public awareness and catalyzing positive changes. My presentation delves into the utilization of multimodal elements in Greenpeace’s video narratives to unveil ecological vulnerability and implement a Cascade Effect Strategy. The talk underscores that the climate crisis acts as a catalyst, heightening existing social, economic, and political challenges and interweaving them into a complex network known as a polycrisis. The Cascade Effect Strategy involves a narrative technique that encompasses visual, auditory, and textual elements, aiming to decipher their persuasive effects in addressing ecological challenges. The corpus comprises 165 videos, containing verbal, nonverbal, and cinematic resources to construct a narrative about the polycrisis. By employing multimodal discourse analysis, this study aims to reveal multimodal patterns in the construction of the cascade effect within Greenpeace’s videos. The research posits that all modes and semiotic resources contribute equally to the intricate semiotic entity. Their integration is linked to the shared knowledge of the audience and is influenced by social and cultural factors. In my presentation, I will delve into several research questions, aiming to uncover the meaning- making potential of semiotic resources employed in constructing the Cascade Effect Strategy. I will explore how these resources interact to form multimodal blends and examine the tactics utilized to implement the Cascade Effect Strategy. The strategic use of verbal semiotic resources involves the intentional fusion of logical reasoning and emotional impact through both explicit and implicit deployment of lexical and rhetorical tools while nonverbal and cinematic resources contribute affective elements to the video, The results contribute to the burgeoning field of environmental communication by unraveling the semiotic complexities of ecological vulnerability representation in Greenpeace’s video narratives and shed light on the potential of multimodal storytelling.

У сучасному екологічному дискурсі ефективна комунікація екологічної вразливості відіграє ключову роль у формуванні громадської обізнаності та каталізації позитивних змін. Моя презентація присвячена використанню мультимодальних елементів у відеооповідях Грінпіс, ​​ розкриваючи екологічну вразливість через реалізацію стратегії каскадного ефекту. У доповіді підкреслюється, що кліматична криза діє як каталізатор, посилюючи існуючі соціальні, економічні та політичні виклики та вплітаючи їх у складну мережу, відому як полікриза. Стратегія каскадного ефекту передбачає наративну техніку, яка охоплює візуальні, слухові та текстові елементи з метою розшифрувати їх переконливий ефект у вирішенні екологічних проблем. Корпус складається з 165 відео, які містять вербальні, невербальні та кінематографічні ресурси для побудови наративу про полікризу. Використовуючи аналіз мультимодального дискурсу, це дослідження спрямоване на виявлення мультимодальних моделей у побудові каскадного ефекту у відео Грінпіс. Дослідження стверджує, що всі модуси та семіотичні ресурси однаково сприяють складній семіотичній сутності. Їх інтеграція пов’язана зі спільними знаннями аудиторії та на неї впливають соціальні та культурні фактори. У своїй презентації я заглиблюся в кілька дослідницьких питань, маючи на меті розкрити смислотворчий потенціал семіотичних ресурсів, які використовуються для побудови стратегії каскадного ефекту. Я досліджуватиму, як ці ресурси взаємодіють для формування мультимодальних сумішей, і досліджуватиму тактику, що використовується для реалізації стратегії каскадного ефекту. Стратегічне використання вербальних семіотичних ресурсів передбачає навмисне злиття логічних міркувань і емоційного впливу за допомогою як явного, так і неявного використання лексичних і риторичних засобів, тоді як невербальні та кінематографічні ресурси вносять у відео афективні елементи, Результати сприяють зростанню сфери екологічної комунікації, розгадуючи семіотичні складності репрезентації екологічної вразливості у відеооповідях Грінпіс і проливаючи світло на потенціал мультимодального оповідання.
Tetiana Krysanova Unveiling Ecological Vulnerability: multimodal construction of cascade effect strategy in Greenpeace’s video narratives Ramaz Kurdadze, Maia Lomia, Ketevan Margiani, Nino Tchumburidze The Function of Prosodic Means in Speech Ojārs Lāms, Elvis Friks Beyond Homeland: literary representations of Latvian (post)exile and post-Soviet Latvia Antra Leine Directions and Challenges of AI-Enhanced Literary Studies Inta Līsmane, Ilze Ruža Ecology of Language: the characteristics of oral communication in doctor’s profession Gunta Ločmele Impact of Technologies on the Latvian Language of Advertising Laimdota Ločmele, Ruta Svētiņa Acquisition and Use of Individual Professional Literature Reading Skills of ESP Students Liliya Makovskaya Error Analysis of Multilingual Students’ Writing in Uzbekistan Merit Maran, Tatjana Menise Fear of the Troubling Futures: eco-anxiety narratives in Estonian and Latvian mediasphere Aya Masmoudi Transculturality, Ecocritical Romanticism, and Existential Philosophy in Kahlil Gibran’s The Prophet (1923)
Keywords: стратегія каскадного ефекту; cascade effect strategy; Грінпіс; Greenpeace; мультимодальність; multimodality; відео; video